การพัฒนารูปแบบการเรียนการสอนโดยบูรณาการแนวคิดการเรียนรู้โดยใช้ปัญหาเป็นฐานและแนวคิดการเรียนรู้ร่วมกันเพื่อส่งเสริมความสามารถในการแก้ปัญหา การสื่อสาร และการเชื่อมโยงทางคณิตศาสตร์ของนักเรียนประถมศึกษาปีที่ 6 - สุภาภรณ์ ใจสุข (จุฬาลงกรณ์มหาวิทยาลัย, 2012)
This research aimed (1) to develop instructional model by integrating problem-based learning approach and collaborative learning approach to enhance mathematical problem solving, communication, and connection abilities of sixth grade students, and (2) to study the effects of the use of the instructional model developed by integrating problem-based learning and collaborative learning approaches to enhance mathematical problem solving, communication, and connection abilities of sixth grade students. The research procedure included two steps. The first step was the development of instructional model and the second step was the experiment of the developed instructional model in classroom. Integrating problem-based learning approach and collaborative learning approach and also analyzing and synthesizing the related concepts, theories, and researches were brought to develop the model. The instructional model was further experimented with the sample group of sixth grade students. The samples had two classrooms, one experimental group and one control group, and 24 students for each classroom, at Wat Taranaram School under the Second Suratthani Primary Educational Service Area office 2. The experimental period is 38 hours with the research tools, including the lesson plans under the developed model and conventional lesson plans and tests for mathematics problem-solving, communication, and connection abilities. Quantitative data were analyzed by means of arithmetic mean (x), standard deviation (S.D.) and t-test and qualitative data were analyzed by content analysis. The research results were summarized as follows:- 1.The developed instructional model included 4 elements, including (1) principles, (2) objectives, (3) steps of instructional process, and (4) learning assessment and evaluation. In addition, the instructional process had 4 steps, including (1) encouraging students’ attention in encountering challenging problems, (2) practicing enthusiastically for searching knowledge, (3) collaboratively examining their knowledge and concluding by group consensus, and (4) applying the knowledge. 2.The developed instructional model is efficient and could be used to enhance students’ mathematical problem solving, communication, and connection abilities, including : 2.1 Mathematical problem solving, communication, and connection abilities at the post-learning stage of the experimental group were significantly higher than those of the control group at the significant level of .05 2.2 Mathematical problem solving, communication, and connection abilities of the experimental group at the post-learning stage were significantly higher than those abilities at the pre-learning stage at the significant level of .05 2.3 According to qualitative analysis, it was found that the experimental group possessed significant development in the abilities of mathematical problem solving, communication, connection continuously and gradually. They had better abilities in solving mathematical problems, communicating, and connecting their mathematical knowledge and principles to solve problems.